+0  
 
0
60
6
avatar

T^3 = 27 * R^5 is simplified to T=a*R^b

a. Calculate the exact values of a and b 

b. If R gets eight times bigger, how many times does T get bigger?

c. The equation for T is simplified to R=p*T^q. Calculate p to one decimal place and q exact. 

 Feb 20, 2020
 #1
avatar+109561 
+2

T^3 = 27 * R^5 is simplified to T=a*R^b

a. Calculate the exact values of a and b 

b. If R gets eight times bigger, how many times does T get bigger?

c. The equation for T is simplified to R=p*T^q. Calculate p to one decimal place and q exact. 

 

 

a.   T^3  =  27 * R^5          take the cube root of both sides

 

T  = 27^(1/3) * (R^5)^(1/3)

 

T  =  [ 3 R^(5/3)  ]      so......   a = 3   and  b  =(5/3)

 

 

b.   3 *  (8R)^(5/3) =

 

       3 * (8)^(5/3) * (r)^(5/3)  = 

 

       3 * ( 8 ^(1/3))^5 * R^(5/3)  =

 

       3*  (2)^5  * R^(5/3)  =

 

       32  *  [ 3 * R^(5/3) ]

 

So....T  will  increase  by   32  times  when R increases by 8 times

 

 

c.  Sorry.....I don't  know the answer to this one.....

 

 

cool cool cool

 Feb 20, 2020
 #2
avatar
+1

Thanks for the help! It's okay :-)

Guest Feb 20, 2020
 #3
avatar+108727 
+1

\(R=p*T^q\\ \)
\(T=3R^{(5/3)}\\ \frac{T}{3}=R^{(5/3)}\\ (\frac{T}{3})^{(3/5)}=R\\ R=(\frac{T}{3})^{(3/5)}\\ R=(\frac{1}{3})^{(3/5)}*T^{(3/5)} \\~\\ p=(\frac{1}{3})^{(3/5)}\\ p=3^{(-0.6)}\\ p\approx 0.517\\~\\ p\approx 0.5\qquad(1\;dec\;place)\\ q=3/5=0.6\qquad (exact) \)

.
 Feb 20, 2020
 #4
avatar
+1

Hi thanks for the reply! This might sound stupid but I was able to follow it all until the p=(1/3)^(3/5). How do you get from this to p=3(-0,6)?

Guest Feb 20, 2020
 #6
avatar+108727 
+1

It is never stupid to ask a genuine question.  However, if you do not understand then it would be stupid to not ask.   wink

 

\(x^{-y}=\frac{1}{x^y}\\ p^{-2}=\frac{1}{p^2}\\ etc\\ \text{that is what a negative power means}\\ so\\ (\frac{1}{3})^{3/5}\\ =(\frac{1}{3})^{0.6}\\ =\frac{1}{3^{0.6}}\\ =3^{-0.6}\)

 

--------------------

 

Think about how index laws work

 

\(x^3\div x^7=x^{3-7}=x^{-4}\\ but\\ x^3\div x^7=\frac{x^3}{x^7}=\frac{xxx}{xxxxxxx}=\frac{1}{x^4}\\ therefore\\ x^{-4}=\frac{1}{x^4}\\\)

 

By the way, your post was blanked out because you used the word 'stupid'

It was blanked out for me too but I have the power to unblank  wink

Melody  Feb 20, 2020
edited by Melody  Feb 20, 2020

11 Online Users

avatar